2018
DOI: 10.1007/s41981-018-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequential α-lithiation and aerobic oxidation of an arylacetic acid - continuous-flow synthesis of cyclopentyl mandelic acid

Abstract: The development of a multistep continuous-flow process, consisting of a direct α-lithiation stage and subsequent hydroxylation by aerobic oxidation, is reported. The protocol is applied to the synthesis of cyclopentylmandelic acid (CPMA), the main building block for the anticholinergic glycopyrronium bromide (glycopyrrolate). We demonstrate the safe utilization of organolithium reagents and molecular oxygen in combination by using a continuous-flow protocol. The first stage involves the formation of a di-lithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Work by Luisi and co-workers illustrates the use of nHexLi in a continuous flow system to generate a dilithium enolate intermediate pivotal in the synthesis of cyclopentyl mandelic acid (CPMA, 41). 53 The authors describe a telescoped process in which nHexLi and phenylcyclopentylacetic acid are mixed in a coiled reactor at 20 °C for a residence time of 5 min to yield the dilithium enolate intermediate. The flow platform designed uses syringe pumps to feed the reagents to the system and a sample loop to deliver nHexLi to the system.…”
Section: ■ Lithium Bis(trimethylsilyl)amidementioning
confidence: 99%
“…Work by Luisi and co-workers illustrates the use of nHexLi in a continuous flow system to generate a dilithium enolate intermediate pivotal in the synthesis of cyclopentyl mandelic acid (CPMA, 41). 53 The authors describe a telescoped process in which nHexLi and phenylcyclopentylacetic acid are mixed in a coiled reactor at 20 °C for a residence time of 5 min to yield the dilithium enolate intermediate. The flow platform designed uses syringe pumps to feed the reagents to the system and a sample loop to deliver nHexLi to the system.…”
Section: ■ Lithium Bis(trimethylsilyl)amidementioning
confidence: 99%
“…The existing manufacturing routes utilize Grignard reagents to afford CPMA in 28–56% yield. Kappe, Luisi and co-workers devised a flow protocol for the sequential α -lithiation and subsequent hydroxylation of α -phenylcyclopentylacetic acid by aerobic oxidation (Scheme 19) [73]. Hexyllithium was utilized as a cost-effective and industrially safe base.…”
Section: Organomagnesium and Organolithium Reagentsmentioning
confidence: 99%
“…A schematic outline of the reactor used in this study is shown in Figure 1. reaction routes that would otherwise only be feasible under regular batch conditions, e.g., higher temperature and pressure than can be used under safe conditions [47][48][49][50][51][52][53][54][55][56][57]. Whilst acetonitrile is a common solvent and is generally used in various fields of chemistry as eluent [41] and polar aprotic organic solvent [58], it is rarely used as reagent in organic chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, more efficient and selective reaction can be carried out in continuous systems than in regular batch operations [41][42][43][44][45][46]. Additionally, flow reaction conditions can enable reaction routes that would otherwise only be feasible under regular batch conditions, e.g., higher temperature and pressure than can be used under safe conditions [47][48][49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%